Influence of scan line spacing on nanosecond pulse laser welding of 6063 Al to steel thin sheets. (January 2022) - Shu, Fengyuan; Niu, Sicheng; Zhu, Baohua; Wu, Laijun; Xia, Hongbo; Chen, Bo; Zhao, Junming; Tan, Caiwang
Highlights: Nanosecond pulse laser welding of steel to Al thin sheets was achieved. Highest lap shear force of 158.8 N was obtained at the line spacing of 0.06 mm. Three fracture modes produced at various line spacings were clarified. The effect of heat accumulation on joining process was elucidated. Abstract: Nanosecond pulsed laser welding of 316L stainless steel and 6063 aluminum alloy thin sheets was performed. The influence of scan line spacing on the joining process was clarified. Large explosive hole and hot cracking defects including radial cracks and arc-shaped cracks occurred in the joint caused by excessive heat accumulation when the line spacing was 0.02 mm. The joints without oxidation were obtained. The thermal-induced penetration increment (TIPI) decreased with the increase of line spacing and reached the maximum value of about 162.24% with the line spacing of 0.02 mm. Fe2 Al5 and FeAl phases probably were produced at all the line spacings. However, FeAl and α-Fe phases in the form of banding structures were possibly generated only with the line spacing of no less than 0.06 mm. The shear force test results indicated that the maximum shear load of 158.8 N was achieved at the line spacing of 0.06 mm due to the large bonding area and fewer defects. Three fracture paths, namely, button pullout failure (BPF), interfacial failure (IF) and mixed fracture (MF) mode of BPF and IF were produced. The heat affected zone was the origin of BPF mode. Local deformation, pores and Fe-Al brittle phases led to the fracture paths of IF and MF.